Perchlorate‐specific proteomic stress responses of Debaryomyces hansenii could enable microbial survival in Martian brines. (10th August 2022) - Heinz, Jacob; Doellinger, Joerg; Maus, Deborah; Schneider, Andy; Lasch, Peter; Grossart, Hans‐Peter; Schulze‐Makuch, Dirk
Abstract: If life exists on Mars, it would face several challenges including the presence of perchlorates, which destabilize biomacromolecules by inducing chaotropic stress. However, little is known about perchlorate toxicity for microorganisms on the cellular level. Here, we present the first proteomic investigation on the perchlorate‐specific stress responses of the halotolerant yeast Debaryomyces hansenii and compare these to generally known salt stress adaptations. We found that the responses to NaCl and NaClO4 ‐induced stresses share many common metabolic features, for example, signalling pathways, elevated energy metabolism, or osmolyte biosynthesis. Nevertheless, several new perchlorate‐specific stress responses could be identified, such as protein glycosylation and cell wall remodulations, presumably in order to stabilize protein structures and the cell envelope. These stress responses would also be relevant for putative life on Mars, which—given the environmental conditions—likely developed chaotropic defence strategies such as stabilized confirmations of biomacromolecules or the formation of cell clusters.